DOZ047.98: The role of laryngeal electromyography in differential diagnosis of vocal cord immobility: a case report. (24th June 2019) - Salvati, A; Trozzi, M; Meucci, D; Tropiano, M L; Bottero, S
Abstract: Object: The term 'vocal cord immobility' (VCI) encompasses both vocal cord paralysis and crico-arytenoid joint ankylosis (CAJA). Bilateral VCI represents an emergency condition characterized by stridor and respiratory distress sometimes requiring tracheostomy to ensure an adequate and safe airway. The aim of this study is to describe the diagnostic and therapeutic management of a rare case of congenital bilateral CAJA in a patient without pregnancy complications, perinatal traumas, or other comorbidities. Materials and Methods: The patient was born full term by C-section after a healthy pregnancy (BW 3270 g, APGAR 9 at 5'). After birth she presented severe stridor with respiratory distress. She was admitted to our hospital when she was 3 months old. The diagnostic assessment was performed with airway endoscopy, pulmonary function tests (PFT), sleep study, echocardiogram, neurological evaluation, chest computed tomography (CT) scan, and brain magnetic resonance imaging (MRI). Laryngeal electromyography (LEMG) with endoscopic placement of Hookwire electrodes was carried out for the differential diagnosis between paralysis and ankylosis and the subsequent choice of the treatment. PFT and sleep study were repeated after each endoscopic procedure. Results: The first airway endoscopy showed bilateral VCI in paramedian position and palpatory evidence of bilateral crico-arytenoid joint fixation. PFT highlighted inspiratory obstruction at the flow/volume and flow/time curves and tidal volume reduction. Sleep study was indicative of mild–moderate obstructive apnea. Echocardiogram, neurological evaluation, brain MRI, and chest CT scan did not detect anomalies. LEMG showed continuous low-amplitude basal activity in all analyzed muscles, in the absence of spontaneous neurotonic activations. Motor evoked potentials (MEP) denoted normal left response and minimum right delay. Two glottic dilations were performed with 7 and 8 mm balloons determining the decrease of stridor and good respiratory balance confirmed by PFT. Endoscopy showed a slight recovery of laryngeal motility. Conclusion: The management of this rare clinical case points out the crucial role of a careful and complete endoscopic examination including the palpation of the crico-arytenoid joints. Moreover LEMG represents an important instrument for the correct differential diagnosis in VCI. In the future the use of LEMG could be mandatory in pediatric patients in order to avoid tracheotomy in favor of more conservative procedures.